The Effect of Urine Concentration and pH on the Growth of Escherichia Coli in Canine Urine In Vitro. (22nd February 2018) - Thornton, L.A.; Burchell, R.K.; Burton, S.E.; Lopez‐Villalobos, N.; Pereira, D.; MacEwan, I.; Fang, C.; Hatmodjo, A.C.; Nelson, M.A.; Grinberg, A.; Velathanthiri, N.; Gal, A.
Abstract : Background: Lower urinary tract infections are common in dogs, and Escherichia coli is the most common bacterial pathogen isolated. The literature has conflicting evidence regarding the inhibitory effects of urine concentration and pH on E. coli growth. Hypothesis/Objectives: To determine the effect of different pH and urine concentrations on E. coli growth in vitro. Animals: Voided urine samples from 10 apparently healthy spayed female dogs were used. Methods: A matrix of 9 urine specific gravity (USG; 1.010, 1.020, and 1.030) and pH (5.5, 7.0, and 8.5) combinations was prepared by diluting and titrating filtered voided urine samples. Three E. coli isolates were obtained from urine of female dogs with signs of lower urinary tract infection and cultured at different urine pH and USG combinations in wells of a microtiter plate. The number of E. coli colony‐forming units (CFU) per mL of urine was calculated after aerobic incubation of the urine at 37°C for 18 hours, and statistically compared. Results: Significant differences were identified in the mean log CFU/mL among different combinations of pH and USG. The lowest log CFU/mL were observed in alkaline concentrated urine (pH 8.5 and USG 1.030). Conclusions and Clinical Importance: Escherichia coli in vitro growth was higher in neutral to acidic and diluted urine compared to alkaline and concentrated urine. The impact of non‐alkalizing diluting diets on the incidence of E. coli lower urinary tract infections should be further explored.